COAL TAR WASTE UTILIZATION BY CRACKING INTO FUEL SOURCE AND ITS SEPARATION USING FRACTIONAL VACUUM DISTILLATION METHOD AND ITS KINETIC STUDY - Ratnaningsih, Wahyu
Coal tar is a hazardous and toxic waste, a by-product of coal gasification processes. Coal tar is a liquid waste produced in industrial fields such as steel, power plant, and cement industry. Coal tar is a black liquid , has a sharp and unpleasant odor, and it is a source of soil contamination because of its difficulty to perform degradation. Hence, it is a necessary to conduct coal tar utilization since this feedstock is abundant. Coal tar has a complex structure contains various kinds of hydrocarbon compounds with different functional groups as it seen as a potential source for fuel. Utilization of coal tar is needed, since coal tar is part of hazardous and toxic waste according to Government Regulation of the Republic of Indonesia No 101 of 2014 on Hazardous Waste Management, with the type of coal industry / processing through pyrolysis-coke production besides of its potential. This research is aimed to utilize coal tar by by cracking it into fuel source and to separate the fuel fraction using fractional vacuum distillation method.